Morphometric analysis of glomeruli, clinical features and outcome in obese and non-obese patients with focal segmental glomerulosclerosis patients - Jordanova, Elena Angel; Janković, Radmila; Naumović, Radomir; Ćelić, Dejan; Ljubičić, Bojana; Simić Ogrizović, Sanja; Basta Jovanović, Gordana (Vojnosanitetski pregled, 2021)
Background/Aim. In the past three decades, focal segmental glomerulosclerosis (FSGS) was commonly regarded as a part of obesity-related glomerulopathy (ORG), a distinct entity featuring proteinuria, glomerulomegaly, progressive glomerulosclerosis, and a decline of renal function. The present study aimed to evaluate the glomerular morphometry, clinical features, and a two-year outcome in the obese and non-obese FSGS patients. Methods. The study included 35 FSGS patients (23 males, aged 46.5 ± 15.2 years) divided into two groups: obese [body mass index (BMI) ≥ 27 kg/m2 (18 patients, aged 47.2 ± 15.5 years)] and non-obese [BMI < 27 kg/m2 (17 patients, aged 45.7 ± 15.2 years)]. The serum concentrations of proteins, albumin, cholesterol, triglyceride, and creatinine were determined at the time of the biopsy, and 6, 12, and 24 months after the biopsy. Cockcroft-Gault (BMI < 27 kg/m2) and Cockcroft-GaultLBW (BMI ≥ 27 kg/m2) formulas were calculated. Glomerular radius (GR), glomerular volume (GV), and glomerular density (GD) were compared morphometrically between the two groups. Results. At the time of the kidney biopsy and 6 months later, the obese had significantly lower glomerular filtration rate (GFR) compared to the non-obese. After 24 months of follow-up, there were not any differences between the groups. The obese had a significantly higher GR (109.44 ± 6.03 μm vs. 98.53 ± 14.38 μm) and GV (3.13 ± 0.49 × 106 μm3 vs. 2.26 ± 0.83 × 106 μm3), and only slightly lower GD (1.91 ± 0.39/mm2 vs. 1.95 ± 0.61/mm2) compared to the non-obese. A significant positive association between GV and BMI (r = 0.439) was found. After 12 months of follow-up, a significantly higher percentage of the non-obese patients reached complete remission compared to the obese (71.4% vs. 37.5%, respectively; p = 0.041), but after 24 months there were no significant differences. Conclusion. Obese patients, at the time of the kidney biopsy and 6 months later, had already a significantly lower kidney function compared to the non-obese ones. However, 12 and 24 months after, this difference was not statistically significant. Also, 24 months after, there was no significant difference between the two groups in the percentage of patients with complete remission of the nephrotic syndrome.